2011
DOI: 10.3109/17453674.2011.625535
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular vs. extraarticular ropivacaine infusion following high-dose local infiltration analgesia after total knee arthroplasty

Abstract: Background and purpose Ropivacaine infusion following high-volume local infiltration analgesia has been shown to be effective after total knee arthroplasty, but the optimum site of administration of ropivacaine has not been evaluated. We compared the effects of intraarticular and extraarticular adminstration of the local anesthetic for postoperative supplementation of high-volume local infiltration analgesia.Patients and methods In this double-blind study, 36 rheumatic patients aged 51–78 years with physical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…Differing modes of delivery/infiltration and/or types of analgesic agents aim to promote an increased ability for the patient to mobilize earlier (for example by reducing pain associated with movement or reducing post operative nausea) which may further increase the likelihood of achieving safe and effective early mobilization. [24][25][26][27] Our findings are similar to other evidence from other research designs not included in our review. An observational design found initiating physiotherapy in total hip arthroplasty on day of surgery reduced length of stay by 0.2 days.…”
Section: Study or Subgroupsupporting
confidence: 94%
“…Differing modes of delivery/infiltration and/or types of analgesic agents aim to promote an increased ability for the patient to mobilize earlier (for example by reducing pain associated with movement or reducing post operative nausea) which may further increase the likelihood of achieving safe and effective early mobilization. [24][25][26][27] Our findings are similar to other evidence from other research designs not included in our review. An observational design found initiating physiotherapy in total hip arthroplasty on day of surgery reduced length of stay by 0.2 days.…”
Section: Study or Subgroupsupporting
confidence: 94%
“…Andersen et al [31] compared the extraarticular wound infiltration or intraarticularly LIA after TKA and found there was no statistical difference between the two groups. Dobrydnjov et al [32] compared the effects of continuous intraarticular and extraarticular adminstration of LIA following TKA and reported that continuous intraarticular reduced the incidence of high pain intensity during first exercises. Future studies should continue to investigate which optimal site of administration is better.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative to periarticular administration of analgesics, intraarticular delivery of anesthetics has gained recent attention. The optimal site for analgesic infiltration, whether it is given intra-or periarticularly, is still unclear [2,6]. Nonetheless, an intraarticular continuous infusion of ropivacaine, in particular, has been shown to be efficacious in reducing postoperative pain and opioid requirements when compared to placebo in prior studies [8,15].…”
Section: Introductionmentioning
confidence: 99%